Analysis of the 2016 – 2025 fiscal budget of U.S. Centers for Disease Control and Prevention - Nana LIU; Lieyu HUANG; Yuan DANG; Zekai YU; Qianqiu LIU; Yan GUO (Zhongguo gonggong weisheng)
ObjectiveTo analyze the changes and trends in the fiscal budget of U.S. Centers for Disease Control and Prevention (CDC) from 2016 to 2025, and to provide a reference for the fiscal budget management of disease prevention and control institutions and public health work in China. MethodsBased on the fiscal budget report data from 2016 to 2025 published on the official website of the CDC, descriptive statistical methods such as time series analysis, structural comparison, and trend analysis were used to understand the CDC′s funding input and allocation in the field of public health from 2016 to 2025. ResultsThe total presidential budget of the CDC showed a fluctuating growth trend from 2016 to 2025, with the lowest value in 2018 (US$ 11.059 billion) and the highest value in 2023 (US$ 47.469 billion). From 2016 to 2025, the allocation of basic funds/project budgets mainly focused on areas such as "HIV/AIDS, Viral Hepatitis, STD, and TB Prevention," "Chronic Disease Prevention and Health Promotion," and "Immunization and Respiratory Diseases," all accounting for more than 10% of the total budget. Among them, the budget for "HIV/AIDS, Viral Hepatitis, STD, and TB Prevention" showed significant fluctuations (US$ 0.934 billion to US$ 1.553 billion), while the budget for "Immunization and Respiratory Diseases" remained at a relatively high level with minor fluctuations (US$ 0.701 billion to US$ 1.256 billion). The budget for "Birth Defects, Developmental Disabilities, Disabilities and Health" remained at a relatively low level with minor fluctuations (US$ 0.100 billion to US$ 0.223 billion). ConclusionsThe CDC continues to promote the integration of public health tasks and dynamically optimize the setting of fiscal budget items. It actively seeks financial support and establishes a needs-matched, project-driven financial support and response mechanism. It strengthens interdepartmental and international cooperation to effectively improve the capacity to respond to health challenges. It supports technological advancement and effective decision-making by emphasizing data and research.